1987
DOI: 10.1126/science.3500514
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of HIV-1 Infectivity by a Soluble, Secreted Form of the CD4 Antigen

Abstract: The initial event in the infection of human T lymphocytes, macrophages, and other cells by human immunodeficiency virus (HIV-1) is the attachment of the HIV-1 envelope glycoprotein gp120 to its cellular receptor, CD4. As a step toward designing antagonists of this binding event, soluble, secreted forms of CD4 were produced by transfection of mammalian cells with vectors encoding versions of CD4 lacking its transmembrane and cytoplasmic domains. The soluble CD4 so produced binds gp120 with an affinity and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(207 citation statements)
references
References 28 publications
6
201
0
Order By: Relevance
“…Nef-defective virions contained higher levels of CD4 than wild-type HIV-1. Infection by HIV-1 laboratory strains (predominately X4 tropic) is more susceptible to inhibition by sCD4 than are HIV-1 primary isolates (which are normally R5 tropic) (21,49,62). We hypothesized that virion-associated CD4 more potently inhibits infection by X4-tropic viruses, thereby preferentially inhibiting replication of nef-defective X4-tropic replication.…”
Section: Vol 78 2004mentioning
confidence: 99%
“…Nef-defective virions contained higher levels of CD4 than wild-type HIV-1. Infection by HIV-1 laboratory strains (predominately X4 tropic) is more susceptible to inhibition by sCD4 than are HIV-1 primary isolates (which are normally R5 tropic) (21,49,62). We hypothesized that virion-associated CD4 more potently inhibits infection by X4-tropic viruses, thereby preferentially inhibiting replication of nef-defective X4-tropic replication.…”
Section: Vol 78 2004mentioning
confidence: 99%
“…Early efforts to block HIV-1 entry to cells focused on using sCD4 to inhibit virus infection (29,30). Although sCD4 demonstrated efficacy against many laboratory strains, it exhibited poor activity against primary isolates (31), which may have contributed to disappointing results in clinical trials (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of studies have previously shown that CD4 is the major receptor for human immunodeficiency virus (HIV) Smith et al, 1987;Lifson et al, 1988), the causative agent of the acquired immunodeficiency syndrome (AIDS) (Fauci, 1988). Infection of T cells with HIV is known to involve the binding of the viral envelope glycoprotein (gpl 20) to CD4 Smith et aL, 1987;Lifson et al, 1988). Thus anti-CD4 monoclonal antibodies and synthetic CD4 oligopeptides have recently been used to map the virus binding site on the CD4 molecule.…”
Section: Introductionmentioning
confidence: 99%